Land Value Taxation in Vancouver: Rent‐Seeking and the Tax Revolt. (11th January 2018) - England, Christopher
Abstract: At the beginning of the 20 th century, Vancouver obtained international acclaim as a "single‐tax" city. Supporters claimed that land value taxation was responsible for the spectacular growth of the city. Even critics believed that it had produced a building boom and declining rents. Yet, over several decades, the system was scaled back and ultimately ended in 1984. This article argues that the property tax revolt can be understood with Mancur Olson's model of collective action. Property owners are better organized than other parties impacted by housing policy because they have financial resources and a salient economic concern in housing. Thus, the special interests of property owners in higher values and unrestricted use prevailed over the interests of tenants and prospective buyers. While the property tax revolt was often articulated in the progressive language of ability to pay, when confronted with progressive counterarguments, it collapsed into explicit arguments for rent‐seeking.